Assessment of regional sacral bone quality: A step towards patient‐specific fracture fixation. Issue 1 (25th March 2022) - Mand, Simran; Telfer, Scott; Battan, Shamele; Brunnquell, Christina L.; Linnau, Ken F.; Zamora, David; Kleweno, Conor P.
Abstract: Characterizing changes in sacral bone density could help us to inform instrumentation choices for procedures involving the sacrum. The aim of this study is to provide detailed maps of changes in sacral bone density across a series of patients using opportunistic quantitative computed tomography (QCT). We hypothesized that there would be significant differences in local cortical and trabecular bone density associated with age and sex. Fifty‐four three‐dimensional sacral models were segmented from routine clinical computed tomography scans, and detailed bone density estimates were derived for each bone using a calibrated opportunistic QCT approach. The effects of age and sex on cortical and trabecular bone density were determined across the sample. Overall cortical bone loss averaged 2.1 and 0.9 mg/cc per year, and trabecular bone loss was 1.6 and 0.7 mg/cc for female and males, respectively. Several regions had loss rates several times greater. Areas that were significantly affected by age included the vertebral bodies, bilateral ala, apex, and areas adjacent to both the anterior and posterior sacral foramina. Areas that were significantly affected by sex were the anterior sacral promontory, aspects of the ala. Bone density distribution across the sacrum changes nonuniformly due to factors including sex and age. Despite these overall trends, there remains significant variability between individuals. Clinical significance: This study provides detailed bone density information for both cortical and trabecular bone that could assist orthopaedic surgeons in planning surgical approaches to sacral fracture fixation.